การพัฒนาโรงแรมที่มีอาคารอนุรักษ์อายุมากกว่า 100 ปี ให้เป็นส่วนหนึ่งของโรงแรม:กรณีศึกษา โรงแรมระรินจินดา เวลล์เนส สปาแอนด์รีสอร์ท และ อนันตรา เชียงใหม่ รีสอร์ท จังหวัดเชียงใหม่ - กรัณฑรัตน์ ปรีติประสงค์ (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
This research aimed to study the redevelopment of historical buildings to be converted as part of a hotel to increase marketing and historical value and to explore and solve issues related to their old buildings. Two hotels more than a century old were chosen for this case study. The Rarinjinda Wellness Spa Resort with a building over 140 years old and the Anantara Chiangmai Resort with an old consulate estate approximately one hundred years old. Both hotels were given "Conservation Building" awards from The Association of Siamese Architects under the Royal Patronage of His Majesty the King (ASA). The tools used in the research were interviews with 2 hotel executives, 2 hotel staff, and 14 hotel clients (7 clients from each hotel). The research found that first, the physical conditions of the old buildings are a main concern, which can be seen from the renovations done by both hotels to preserve the original structure of the buildings as much as possible. It is expected that renovations will be able to alleviate future maintenance problems that could occur. Due to structural differences, buildings must be renovated using appropriate methods. One such renovation to repair subsidence required the base of the building be supported. Older materials were replaced while the construction materials used were carefully chosen to match the period style of the original buildings. Second, both hotels exploited the historicism of the buildings as selling points for public marketing purposes. They were promoted as heritage structures in marketing roadshows with clients in European and East Asian countries as target groups. Third, financing used 50 % existing capital/ 50% loans from financial institutions for investment funding. Fourth, both hotels differ in their management structure. The Rarinjinda Wellness Spa Resort uses its own management team under the Siam Wellness Group; in contrast, the Anantara Chiangmai Resort hired Minor International, a hotel management company well-known among 5-star hotels. Finally, regarding upgrading the physical structures of the buildings, 2 issues were addressed: expert architects and skilled construction workers are required for repair and renovation of historical buildings; and secondly, materials and system planning must be selected in accordance with the current function of the building. In addition, Anantara Hotel employed a rebranding strategy using a new name and management team, which affected clients’ perception of the product. Clients were informed via email about the hotel name change to avoid misunderstanding. Finally, as these hotels are historical buildings, it is necessary to be prepared for annual and more frequent maintenance, resulting in higher costs, compared with non-historical buildings.